Housing : Federal policies and programs - Weicher, John C. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1980)
The book attempts to explain federal housing policy and programs in the context of housing market conditions which result primarily from the private decisions of individuals and firms.
Includes bibliographical references.
usc 22/09/2017
Loans
Keywords: Housing policy; Housing subsidies; Home ownership; Federal aid to housing; United States